Karakteristik Marshall Pada Campuran Asphalt Concrete – Wearing Course (AC-WC) Dengan Penambahan Styrofoam - Ika Sulianti; Ibrahim Ibrahim; Agus Subrianto; Adelia Monita; Medici Medici (Sekolah Tinggi Teknik - PLN, 2019)
Styrofoam waste presents the environment issue because it is difficult to decompose. As an effort to recycle this pollutant, styrofoam can be utilized as an additive in asphalt concrete mixture. The use of additives aims to create a flexible pavement layer having good performance and meet the requirements. The purpose of this study is to find out whether the addition of styrofoam can improve the quality of asphalt mixtures, and look for alternative additives that can increase asphalt pavement performance. In this study, researchers used food container styrofoam as an addition and incorforated into Asphalt Concrete Wearing Course (AC-WC) mixture. The styrofoam content was 6.5%; 6.75%; 7% ; 7.25%; and 7.5% of asphalt weight. The optimum asphalt contentused is 5.5%. The value of the optimum stability was 3126,002 kg, found at 7.25% of styrofoam content. The best results of Marshall test was obtained at 6.5% of styrofoam content with stability value 1362,045 kg, VIM value 4,96%, VMA 15,025%, VFA 67,800%, flow 3,44 mm, and MQ 416,338 kg / mm.